Https Doc 0c BK Apps Viewer - Googleusercontent
Https Doc 0c BK Apps Viewer - Googleusercontent
Https Doc 0c BK Apps Viewer - Googleusercontent
of Bartle, The
Elements of Real Analysis, 2/e
Written by Men-Gen Tsai
email: b89902089@ntu.edu.tw
8.. In this project, let {a1 , a2 , ..., an }, and so forth, be sets of n positive
real numbers.
(a) In can be proved (for example, by using the Mean Value Theorem)
that if a and b are positive and 0 < < 1, then
a b1 a + (1 )b
and that the equality holds if and only if a = b. Assume this, let r > 1 and
let s satisfy
1 1
+ = 1,
r s
(so that s > 1 and r + s = rs). Show that if A and B are positive, then
Ar B s
+
,
r
s
and that the equality holds if and only if Ar = B s .
AB
(b) Let {a1 , ..., an } and {b1 , ..., bn } be positive real numbers. If r, s > 1
and (1/r) + (1/s) = 1, establish H
olders Inequality
n
X
aj b j
X
n
j=1
(Hint: Let A = (
bj /B.)
arj
1/r X
n
j=1
brj
1/r
j=1
(c) Using H
olders Inequality, establish Minkowski Inequality
X
n
j=1
(aj + bj )r
1/r
X
n
j=1
arj
1/r
X
n
j=1
brj
1/r
1/r
n
X
aj b j
X
n
j=1
aj
X
n
j=1
bj
j=1
n
1X
arj
n j=1
1/r
n
1X
brj
n j=1
1/r
n
1X
(aj bj )r
n j=1
1/r
Show that this inequality must be reversed of {aj } is increasing and {bj } is
decreasing.
Proof of (a): Let f (x) = x + (1 ) x , where x = a/b. Thus
f 0 (x) = x1 = (1 x1 ).
Hence f (x) attains its minimum at x = 1 (, a = b,) and f (1) = 0. Hence
f (x) = x + (1 ) x 0. Put x = a/b I have
a
a
( ) (1 ) ( ) 0
b
b
2
or
a b1 a + (1 )b.
Next, let = 1/r, a = A1/ , and b = B 1/(1) . Hence
AB
Ar B s
+
.
r
s
arj )1/r , B = (
aj /A and bj /B:
aj b j
1 aj
AB
r A
for all 1 j n. Sum them up:
n
X
aj b j
j=1
AB
r
n
1X
aj
r j=1 A
1 bj
+
s B
r
s
n
1X
bj
s j=1 B
s
n
1 X
aj bj 1.
AB j=1
Thus,
n
X
aj b j
X
n
j=1
arj
1/r X
n
j=1
brj
1/r
j=1
r/s
aj aj + b j
r/s
b j aj + b j
X
arj
X
brj
1/r X
1/r X
(aj + bj )r
r
1/s
1/s
(aj + bj )
Thus
X
X
r
aj + b j
r
(aj + bj )
1/r
X
X
(aj + bj )
arj
1/r
+
3
1/s X
X
brj
arj
1/r
1/r
X
brj
1/r
1
aj
n
j=1
Hence
X
n
arj
1/r X
n
1
( )r
j=1 n
j=1
n
n
1X
1X
aj
ar
n j=1
n j=1 j
1/s
1/r
ai bi + aj bj
j=1 i=1
n
X
(naj bj +
n
X
j=1
n
X
i=1
n
X
j=1
i=1
(aj bj + n
ai b i )
ai bi )
n X
n
X
ai b j
j=1 i=1
n
n
X
X
(bj
ai + aj
j=1
i=1
X
X
n
n
ai
i=1
Hence
n
n
X
+ aj b i
aj b j
j=1
X
n
n
X
bj +
j=1
aj
j=1
bi )
i=1
X
n
X
n
j=1
aj
X
n
bi
i=1
bj
j=1
n
X
j=1
aj b j
X
n
j=1
aj
X
n
j=1
bj
arj
j=1
Hence
n
1X
ar
n j=1 j
1/r
X
n
brj
j=1
n
1X
br
n j=1 j
n
X
(arj brj ).
j=1
1/r
n
1X
(aj bj )r
n j=1
1/r
Also, by the note of part (e), this inequality must be reversed of {aj } is
increasing and {bj } is decreasing.